Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

You may use that $ 1-x^n = (1-x)(x^{n-1} + x^{n-2}+\cdots +x+1)$

Can someone help me with this one? This is what I have so far:

$ f(x) = \dfrac{1}{x^n(1-x)} = \dfrac{A_0}{x}+\dfrac{A_1}{x^2}+\dfrac{A_2}{x^3}+\cdots +\dfrac{A_{n}}{x^n}+\dfrac{A_{n+1}}{1-x}$.

Multiplying through $ x^n(1-x)$, and rearranging, I get something similar to the hint that was given:

$1-A_{n+1}x^n = (1-x)( A_0x^{n-1} + A_1x^{n-2}+ A_2x^{n-3}+\cdots+A_{n-1}x+A_n)$.

Now I am not sure how to proceed, it's only a 2 point question, so it doesn't seem like it should be difficult, but how do I solve for the constants?

I greatly appreciate any help, point in the right direction!

share|cite|improve this question
So, in your last line, if you let $A_i = 1$ for all $i$, you are done by line 1. – martini Sep 26 '12 at 12:04
up vote 4 down vote accepted

$$\tag{1} \frac{1}{x^n(1-x)}=\sum_{k=1}^n\frac{A_k}{x^k}+\frac{A_{n+1}}{1-x}. $$ Multiplying both sides of (1) by $1-x$ and setting $x=1$, we have $A_{n+1}=1$. So now we have for $x \ne 1$: \begin{eqnarray} \sum_{k=1}^n\frac{A_k}{x^k}&=&\frac{1}{x^n(1-x)}-\frac{1}{1-x}=\frac{1}{1-x}\left(\frac{1}{x^n}-1\right)=\frac{1}{1-x}\left(\frac{1}{x}-1\right)\sum_{k=0}^{n-1}\frac{1}{x^k}\cr &=&\frac{1}{x}\sum_{k=0}^{n-1}\frac{1}{x^k}=\sum_{k=1}^n\frac{1}{x^k}, \end{eqnarray} i.e. $A_k=1$ for every $1 \le k \le n+1$, and $$ \frac{1}{x^n(1-x)}=\sum_{k=1}^n\frac{1}{x^k}+\frac{1}{1-x}. $$

share|cite|improve this answer
Thanks for your help Mercy! If I were to then integrate this - how would I go about integrating the first part, with the summation? – JackReacher Sep 26 '12 at 22:02
You just integrate each term, as long as it makes sense! – Mercy King Sep 26 '12 at 22:48

Note that $$ \frac{1}{x^n(1-x)} = \frac{1}{x^n} + \frac{1}{x^{n-1}(1-x)} $$ Now use induction.

share|cite|improve this answer

If we expand right hand side of your last expression, we get $$A_n+(A_{n-1}-A_{n})x+(A_{n-2}-A_{n-1})x^2+\cdots+(A_{1}-A_{0})x^{n-1}-A_0x^{n}.$$ Therefore, we get $$1-A_{n+1}x^n=A_n+(A_{n-1}-A_{n})x+(A_{n-2}-A_{n-1})x^2+\cdots+(A_{1}-A_{0})x^{n-1}-A_0x^{n}.$$ Comparing the coefficients of the like terms, we obtain $$1=A_n, A_{n-1}-A_{n}=0, A_{n-1}-A_{n-2}+0,..., A_{1}-A_{0}=0,\mbox{ and }A_{n+1}=A_0.$$ This implies that $$A_i=1\mbox{ for all }i=0,1,...,n+1.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.